2022
DOI: 10.1080/02813432.2022.2073961
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the feasibility to combine patients with chronic obstructive pulmonary disease and chronic heart failure in self-management groups with focus on exercise self-efficacy

Abstract: Objective To compare the level of exercise self-efficacy, symptoms, functional capacity and health status and investigate the association between these variables in patients with chronic obstructive pulmonary disease (COPD) and chronic heart failure (CHF). Additionally, to investigate how diagnosis, symptoms and patient characteristics are associated with exercise self-efficacy in these patient groups. Design Cross-sectional study. Setting Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…But prior literature showed that patients disclosed decreased self‐efficacy in self‐managing BCRL (Ostby et al, 2018). Evidence revealed that self‐efficacy enhancing programs showed good effects in improving self‐management behaviours of other chronic diseases (Giezeman et al, 2022). Hence, self‐efficacy deserves to be assessed and intervened in LSMB‐enhancing programs.…”
Section: Discussionmentioning
confidence: 99%
“…But prior literature showed that patients disclosed decreased self‐efficacy in self‐managing BCRL (Ostby et al, 2018). Evidence revealed that self‐efficacy enhancing programs showed good effects in improving self‐management behaviours of other chronic diseases (Giezeman et al, 2022). Hence, self‐efficacy deserves to be assessed and intervened in LSMB‐enhancing programs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with heart failure and chronic obstructive pulmonary disease have similar symptoms and functional level [ 24 ]. Undeniably, there is an obvious risk that patients with these symptoms who have not undergone an echocardiogram may be misdiagnosed.…”
Section: Limitationsmentioning
confidence: 99%
“…Previous studies have extensively explored the relationship between CHF and the presence of depression and anxiety symptoms in patients [13]. Multiple studies have reported a higher prevalence of depression and anxiety symptoms among CHF patients compared to the general population.…”
Section: Introductionmentioning
confidence: 99%